1979
DOI: 10.1111/j.1939-0025.1979.tb02582.x
|View full text |Cite
|
Sign up to set email alerts
|

Manic-depressive illness: Psychodynamic features of multigenerational families.

Abstract: Psychodynamic features of families with multigenerational bipolar manic-depressive illness are described. Repetitive maladaptive patterns, including avoidance of affect, unrealistic standards of conformity, absence of intimate relationships apart from family, displaced parental low self-esteem, and fears related to illness heritability, may influence the maintenance of family pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
3
28
0
1
Order By: Relevance
“…Eight studies have examined the parenting and attachment histories of individuals with bipolar disorder and are summarized in Table III. In an early qualitative study, Davenport, Adland, Gold, and Goodwin (1979) noted that six families including both a parent and adult child with bipolar I disorder were characterized by domineering mothers and emotionally or physically absent fathers. Four retrospective, quantitative studies of adults obtained no differences between the reported parenting of bipolar and comparison groups (Cooke, Young, Mohri, Blake, & Joffe, 1999;Joyce, 1984;Parker, 1979;Perris et al, 1986), although two of these found that parenting practices were associated with the course of bipolar disorder.…”
Section: Parenting and Bipolar Disordermentioning
confidence: 98%
“…Eight studies have examined the parenting and attachment histories of individuals with bipolar disorder and are summarized in Table III. In an early qualitative study, Davenport, Adland, Gold, and Goodwin (1979) noted that six families including both a parent and adult child with bipolar I disorder were characterized by domineering mothers and emotionally or physically absent fathers. Four retrospective, quantitative studies of adults obtained no differences between the reported parenting of bipolar and comparison groups (Cooke, Young, Mohri, Blake, & Joffe, 1999;Joyce, 1984;Parker, 1979;Perris et al, 1986), although two of these found that parenting practices were associated with the course of bipolar disorder.…”
Section: Parenting and Bipolar Disordermentioning
confidence: 98%
“…(1) and Davenport et al . (5, 6, 7). These authors examined dynamic features (including child‐rearing practices) of several generations of families in which a manic‐depressive disorder was diagnosed.…”
mentioning
confidence: 99%
“…"Conformity" and denial of emotion in bipolar families have been noted by previous investigators (Cohen et al, 1954;Davenport et al, 1979;Stierlin et al, 1986), but they have been seen as preconditions or causes of the illness rather than as consequences. When more than one generation has been affected by illness, this attitude can be especially pervasive, becoming incorporated into the life and traditions of the family.…”
Section: Constraints On Behaviormentioning
confidence: 77%
“…Previous studies of families with bipolar disorder (Cohen et al, 1954;Davenport et al, 1979;Stierlin et al, 1986) have consistently noted problems in growth and development for family members. Any chronic illness will affect the family in ways that interfere with development (Gonzalez et al, 1989;Rolland, 1987); however, bipolar illness presents specific challenges in this regard.…”
Section: Effect On Growth and Developmentmentioning
confidence: 93%